ОПТИМИЗАЦИЯ УСЛОВИЙ ЛАБОРАТОРНОГО ПОЛУЧЕНИЯ АЦЕТАТА НАТРИЯ ВЫСОКОЙ ЧИСТОТЫ - Сейтназарова, О.М.; Кулдашева, Ш.А.; Абдикамалова, А.Б.; Юсупов, Ж.Т.; Кувватова, Г.Э. (SCIENCE and SOCIETY, 2025)
The article presents the development of a mini-technology for obtaining high-purity sodium acetate based on the interaction of calcium carbonate (CC) and acetic acid (AC) with subsequent replacement of calcium with sodium carbonate. The influence of process parameters (pH, temperature, reagent ratio, mixing rate, and crystallization mode) on product yield and purity was investigated. It was established that the optimal conditions (pH1 = 6.8-7.2; pH2 = 7.5-7.9; melting point 40-45 °C; crystallization point 10-15 °C) provide 82-83% of theoretical yield and 99.5-99.6% sodium acetate purity. The calcium content in the final product does not exceed 0.01%, heavy metals - 0.002%. The developed methodology is distinguished by its ease of implementation, the use of available reagents, and can be implemented in university laboratories and research institutes.